2006
DOI: 10.1097/01.olq.0000221335.80508.fa
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Expanding Harm Reduction Activities for Injecting Drug Users in Odessa, Ukraine

Abstract: At the current coverage, the harm reduction intervention in Odessa is cost-effective but is unlikely to reduce IDU HIV prevalence in the short-term. To reduce HIV prevalence, more resources are needed to increase coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 34 publications
4
46
1
Order By: Relevance
“…NSPs have been shown to be safe and effective in reducing HIV transmission in diverse settings (Bastos & Strathdee, 2000;Jenkins et al, 2001;Kwon et al, 2009;Vickerman et al, 2006;Wodak, 2006). A recent review of reviews found sufficient evidence of NSPs to reduce self-reported risky injecting behavior and tentative evidence of effectiveness of NSPs to reduce HIV transmission (Palmateer et al, 2010).…”
Section: Effectiveness and Cost-effectiveness Of Nspsmentioning
confidence: 99%
“…NSPs have been shown to be safe and effective in reducing HIV transmission in diverse settings (Bastos & Strathdee, 2000;Jenkins et al, 2001;Kwon et al, 2009;Vickerman et al, 2006;Wodak, 2006). A recent review of reviews found sufficient evidence of NSPs to reduce self-reported risky injecting behavior and tentative evidence of effectiveness of NSPs to reduce HIV transmission (Palmateer et al, 2010).…”
Section: Effectiveness and Cost-effectiveness Of Nspsmentioning
confidence: 99%
“…Other biological parameters such as risk of HIV transmission per injection with a shared injection (ÎČ), and effectiveness of syringe cleaning to prevent virus transmission (Δ) were obtained from literature (22)(23)(24)(25)(26)(27)(28)(29)(30). A summary of such parameters for each group, with and without sufficient NSP coverage, is presented in Table 1.…”
Section: Model's Parametersmentioning
confidence: 99%
“…However, transmission of HIV is found largely due to sharing of syringes among drug users and practicing unsafe sex. The activities involved promotion of safe drug use practices and sexual behavior through provision of condoms, syringes and information materials [11]. Apart from preventing the spread of HIV, harm reduction strategies also aim to raise awareness and provide education within the IDU community about HIV and other diseases [12].…”
Section: Harm Reductionmentioning
confidence: 99%
“…These work mostly involved classifying and quantifying the costs of harm reduction, as evident by some literatures. Any costs that relates to detecting and treating of diseases were classified as direct costs whereas costs that relates to any production lost as a result of premature mortality, morbidity and the use of health care services were classified as indirect costs [1].The intervention costs have also been classified as financial costs and economic costs [2]. In measuring the effectiveness of the activities, productivity costs were also introduced which described some indirect costs associated to intervention activities [3].…”
Section: Introductionmentioning
confidence: 99%